Nano-encapsulation and Probiotic Delivery: Emerging Strategies for Non-Dairy Functional Foods and Therapeutic Applications (Development Engineering Conferences Center Articles Database, 2025)
The growing demand for functional foods has led to the development of non-dairy probiotic products that cater to consumers with dietary restrictions or preferences. Nanoencapsulation has emerged as a promising strategy to enhance the stability, bioavailability, and targeted delivery of probiotics, particularly in challenging gastrointestinal environments. This review explores recent advances in nanoencapsulation techniques, focusing on their application in non-dairy matrices and their potential therapeutic roles. Gold nanoparticles (AuNPs) and magnetic nanoparticles (MNPs) have shown significant promise in biomedical applications due to their unique optical and magnetic properties. Their integration with probiotic strains such as Lactobacillus fermentum enables the creation of heterobimetallic systems capable of dual-functionality: photothermal therapy and magnetic hyperthermia. These systems demonstrate efficient heat generation under laser and magnetic field exposure, offering new avenues for oral cancer treatment strategies. The review also highlights the importance of encapsulation materials, including biopolymers and lipid-based carriers, and discusses the physicochemical factors that influence nanoparticle-probiotic interactions. Additionally, regulatory considerations and toxicological evaluations are addressed to ensure the safe incorporation of nanomaterials into food and therapeutic products. While current findings are promising, further studies are needed to optimize nanoparticle design, improve detection methods for bacterial viability, and ensure long-term safety. The potential of Lactobacillus fermentum as a drug carrier opens new possibilities for targeted delivery systems in gastrointestinal therapies, positioning nanoencapsulation as a key technology in the future of functional foods and biomedicine.